Job Safety Analysis sebagai Upaya Pencegahan Kecelakaan Kerja pada Proses Produksi Air Minum Dalam Kemasan - Aminurrohman, Aminurrohman; Mustaqim, Mustaqim; Riyana, Iis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The bottled drinking water (AMDK) industry involves various production activities that carry potential workplace hazards. The main problem is the risk of accidents that may affect worker safety, ranging from machine operation and material handling to ergonomic conditions. Therefore, this study applies the Job Safety Analysis (JSA) method to identify potential hazards and assess risk levels based on their likelihood and consequences. The analysis results show that most hazards fall into the low to medium category, such as slipping or chemical splashes, while several activities, including the use of hot press machines, heavy lifting, and non-ergonomic working positions, are classified as high risk. Based on these findings, the proposed solutions include strengthening supervision, providing regular occupational safety training, ensuring the use of personal protective equipment (PPE), and improving ergonomic aspects, so that worker safety can be better ensured.